Level of quality of life of students with learning disabilities at the secondary school education - Ohud Aldaghmi (Umm Al-Qura University, 2022)
The objective of the current study is to identify the quality of life of the female students with learning disabilities at the secondary school education, especially social, family, education, teaching, occupation and management of time and to identify the most important areas of quality of life. To do it, the researcher prepared a life quality measure and used the analytical, descriptive method. With a sample of 196 female students with learning disabilities at the secondary school education in the Riyadh region, the findings of the study indicated a low level of quality of life in the different areas retained in this paper. They were ranked as follows: 1) the area of the occupation and management of time, 2) the area of quality of family life, followed by 3) the area of quality of social life, and finally 4) the field of education and teaching. Therefore, the quality of education and teaching was the lowest with a mean equal to 15.56, followed by family life with a mean equal to 19.88, while the field of the quality of time occupation and education and the field of quality of social life were the highest with means equal respectively to 20.45 and 31.36.